Clinical trial: Chidamide plus CHOP improve the survival of newly diagnosed angioimmunoblastic T-cell lymphoma - Zong, Xiangping; Yang, Zhen; Zhou, Jin; Jin, Zhengming; Wu, Depei (Frontiers in Immunology, 2024)
Background: Angioimmunoblastic T-cell lymphoma (AITL) is known for its unfavorable survival prognosis. Chidamide has shown efficacy in relapsed/refractory AITL, but its efficacy in newly diagnosed AITL is uncertain. Objective: This retrospective research aimed to evaluate the effectiveness and safety of chidamide when used with doxorubicin, cyclophosphamide, prednisone, and vincristine (CHOP) in comparison to CHOP by itself for individuals newly diagnosed with AITL, and to examine the impact of transplantation. Method: This was an analysis that compared outcomes among patients who received chidamide + CHOP on a clinical trial vs. historical controls who received CHOP alone, enrolling a total of sixty-six treatment-naive AITL patients between April 2014 and November 2022. Among them, thirty-three received chidamide in addition to CHOP (chidamide group), while thirty-three received CHOP alone (control group). The clinical characteristics were balanced between the two groups. All patients were scheduled to undergo up to six courses of treatment before transplantation. Results: The chidamide group had a significantly longer median overall survival (OS) compared to the control group, with a median OS that was not reached, as opposed to 20 months in the control group (p = 0.002). In the control group, the median progression-free survival (PFS) was 11 months, while in the chidamide group, it was 22 months (p = 0.080). In the high-risk group (IPI ≥ 3), the chidamide group demonstrated notably superior complete response (CR) and overall response rate (ORR) compared to the control cohort (p = 0.002, p = 0.034). The PFS and OS in the chidamide group were not reached, and there were significant differences compared to the control group (p = 0.007, p = 0.003). The median OS of the transplanted group was longer than the non-transplanted group (p = 0.004). On multivariate analysis, chidamide group reduced the hazards of death in the total cohort. Conclusion: As the study was non-random and retrospective, Chidamide combined with chemotherapy should be tested in randomized trials given its potential to improve prognosis in treatment-naive AITL patients. Furthermore, autologous hematopoietic stem cell transplantation (auto-HSCT) has demonstrated enhanced overall survival in individuals with AITL.